Impact of health insurance coverage on Chuna Manual Therapy utilization: A cross-sectional analysis using data from the 2017 and 2020 Korean Medicine Utilization and Herbal Medicine Consumption Survey - Hyungsuk Kim; Chunhoo Cheon (PLoS ONE, 2025)
Chuna Manual Therapy (CMT) is a component of traditional Korean Medicine that was integrated into national health insurance coverage of the Republic of Korea in 2019 to improve accessibility. This study investigates the impact of this policy change on CMT utilization patterns using data from the Korean Medicine Utilization and Herbal Medicine Consumption Survey, comparing pre-insurance (2017) and post-insurance (2020) periods. A descriptive cross-sectional analysis was conducted with a nationally representative sample, and logistic regression analysis was used to identify key determinants of CMT utilization. The results show a significant increase in CMT utilization, particularly among outpatients. Notable demographic shifts included an increased utilization among males, individuals with higher education levels, and those employed in professional, service, and skilled labor occupations. While insurance coverage improved accessibility, overall satisfaction with treatment results and costs slightly declined. Musculoskeletal disorders remained the primary conditions treated with CMT. The findings highlight that while insurance coverage expanded access to CMT, its effects on patient satisfaction and healthcare costs require further investigation. Further studies should assess the long-term implications of insurance coverage on both patient outcomes and healthcare provider practices.